Sistema logístico en la Hacienda El Okaso del cantón Rocafuerte Manabí-Ecuador - Colamarco Palma, Angie Pamela (2020)
This research was analyzed at Hacienda El Okaso in the presentation of the logistics system attention generating risks in distribution communication, waste, loss of time in different areas, so it is necessary to structure a system that allows hem to be competitive, obtain sustainable advantages, reduce costs and improve the order-delivery cycle. having as a general objective to structure a logistics system for Hacienda el Okaso that contributes to the improvement of productivity. To carry it out, it was necessary to collect information and analyze bibliographic sources that supported its validation in a scientific way, followed by a field visit to the Hacienda El Okaso and thus learn about each of the processe by observing and applying a characterization sheet applied to the Ministry of the Treasury, using the PHVA cycle. Subsequently, an interview will be needed and will be applied that will obtain quantitative and qualitative information from the Hacienda el Okaso through the information acquired. The degree of relationship of the variables. Once the shortcomings are known, an action plan will be processed applying the 5w + 1h matrix, generating strategies for La Hacienda El Okaso with the proposal of the processes that are most efficient and affected.